Hierarchical porous ceramics with multiple open pores from boehmite gel emulsions. Issue 4 (1st October 2020) - Zheng, Yu; Luo, Xudong; You, Jiegang; Li, Ting; Hou, Qingdong
Abstract: Ceramic foam materials with highly porous microstructure are playing vital role in increasing areas, especially for those with requirements for open channels and superior specific surface area. In this work, a simple and versatile approach to prepare ceramic foams with open pores has been proposed, that is gelation of boehmite nanoparticle‐assembled emulsions. Notably, hierarchical porous microstructure with open channels and uniform pore structure has been built. High specific surface area up to389.4 m 2 /g is attainable, making it excellent adsorption material when combining the merit of hierarchical pore structure. Furthermore, lattice‐shaped ceramics are prepared via direct ink writing gelled emulsion, displaying the potential of forming lightweight material with complex shape and designable macrostructure. The three‐dimensional (3D) printed foams exhibit multiple open pores, which cover length scale from mm scale, to μm scale and nm scale, making them promising materials in several fields like adsorption and gas filtrations, etc.